Retroperitoneal abscess as a presentation of colon cancer: The largest case set analysis to date, which extracted from our unit and the literature - Zhou, Junmin; Wan, Songlin; Li, Chunguang; Ding, Zhao; Qian, Qun; Yu, Hao; Li, Daojiang (Frontiers in Oncology, 2023)
Objective: Colon cancer with retroperitoneal abscessis a rare and easilymisdiagnosed disease and has only been reported via case.There is an urgent need to conduct a dataset analysis for such patients,which is crucial to improving the survival rate and quality of life of these patients Methods:Patients with colon cancer associated with retroperitoneal abscess were extracted from our hospital anddatabases.Clinical information, including the patients' basic characteristics, clinical symptoms, laboratory tests,imaging examinations, treatment methods and prognosis was analyzed.Results: Sixtyone patients were analyzed, with an average age of 65 years. The proportions of right and left colon cancers were 63.9% and 36.1%, respectively.A total of 98.0% of the patients had adenocarcinoma. Many patients have insidious symptoms such as fever and weight loss.At the first medical visit, pain was the most common symptom (71%), with pain in the thigh (21.8%), abdomen (21.8%), and waist and back (14.5%) ranking among the top three. The misdiagnosis rate of the patients referred to our department was 75%, while the overall misdiagnosis rate in the literature was 43.9%. Laboratory tests show that these patients often have elevated white blood cells and anemia.CT examination showed that 87.2% of patients had an iliopsoas muscle abscess, and tumors were not simultaneously detected in 37.2%. A total of 33.9% of patients had local abscesses of the iliopsoas muscle,26.4% had drainage into the subcutaneous tissue of the waist and upper buttocks, and 22.6% had drainage around the adductor muscle group of the thigh.These patients have a variety of treatments, and many patients have undergone multiple and unnecessary treatments.Thirteen patients died after surgery, and 6 died in the hospital, of whom four were patients undergoing direct surgery, and the other 7 died after discharge due to cachexia.Colorectal cancer with retroperitoneal abscess is a relatively rare and easily misdiagnosed subtype of colon cancer.It is more likely to occur in right-sided colon adenocarcinoma.The main clinical symptom is pain caused by the drainage of pus to the corresponding areas of the waist,abdomen,and legs.CT is the preferred diagnostic method. Actively treating the abscess and then transitioning to standard colon cancer treatment can prevent patient death and improve treatment quality.